Oral histoplasmosis: A fungal infection mimicking malignant lesion - M. Sofee, Mohammad S. Bin (Hasanuddin University, 2022)
Abstract: Histoplasmosis is a deep fungal infection that is commonly found in tropical regions. Oral manifestation of histoplasmosis is more often associated with the disseminated form which is commonly seen in immunocompromised individuals. Commonly, oral lesions may present as multiple, granular and painful ulcers as well as verrucous growths mimicking oral carcinoma. We report a case of an avid gardener who presented with a non-healing ulcer over the hard palate with the impression of a sinister lesion. Patient claimed the lesion had persisted for a period of 5 weeks with multiple visits to medical and dental clinic but was unable to reach a definitive diagnosis and treatment. Following referral, initial examination has warranted the clinician at the Department of Oral and Maxillofacial Surgery to proceed for a tissue biopsy revealing oral lesion favouring histoplasmosis. A multidisciplinary approach alongside the Infectious Disease Department was able to devise a proper treatment plan at eradicating the patient’s concern. Following therapy, the oral ulcer healed well with minimal complication.